Crosstalk in oxygen homeostasis networks: SKN-1/NRF inhibits the HIF-1 hypoxia-inducible factor in Caenorhabditis elegans. - Dingxia Feng (Public Library of Science (PLoS), 2021)
During development, homeostasis, and disease, organisms must balance responses that allow adaptation to low oxygen (hypoxia) with those that protect cells from oxidative stress. The evolutionarily conserved hypoxia-inducible factors are central to these processes, as they orchestrate transcriptional responses to oxygen deprivation. Here, we employ genetic strategies in C. elegans to identify stress-responsive genes and pathways that modulate the HIF-1 hypoxia-inducible factor and facilitate oxygen homeostasis. Through a genome-wide RNAi screen, we show that RNAi-mediated mitochondrial or proteasomal dysfunction increases the expression of hypoxia-responsive reporter Pnhr-57::GFP in C. elegans. Interestingly, only a subset of these effects requires hif-1. Of particular importance, we found that skn-1 RNAi increases the expression of hypoxia-responsive reporter Pnhr-57::GFP and elevates HIF-1 protein levels. The SKN-1/NRF transcription factor has been shown to promote oxidative stress resistance. We present evidence that the crosstalk between HIF-1 and SKN-1 is mediated by EGL-9, the prolyl hydroxylase that targets HIF-1 for oxygen-dependent degradation. Treatment that induces SKN-1, such as heat or gsk-3 RNAi, increases expression of a Pegl-9::GFP reporter, and this effect requires skn-1 function and a putative SKN-1 binding site in egl-9 regulatory sequences. Collectively, these data support a model in which SKN-1 promotes egl-9 transcription, thereby inhibiting HIF-1. We propose that this interaction enables animals to adapt quickly to changes in cellular oxygenation and to better survive accompanying oxidative stress.